Pemanfaatan dan Pengelolaan Sistem Informasi Web Profil pada SDK Santo Yosep 1 Kota Kupang - Kornelis Letelay; Yulianto Triwahyuadi Polly; Arfan Y Mauko; Tiwuk Widiastuti; Dony Martinus Sihotang (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
The Community Service (PkM) activity titled “Utilization and Management of Web Profile Information System at SDK Santo Yosep 1 Kota Kupang” involved the partnership with SDK Santo Yosep 1 Kota Kupang. The purpose of this community partnership program was to enhance information technology skills and knowledge for educators and educational staff at SDK Santo Yosep 1 located in Kota Raja sub-district. The methods used in this activity included training on managing the system that had already been developed, specifically on data entry, which would later be published as school information for the general public. Additionally, a questionnaire method was employed to assess the system's effectiveness. The results of the training showed that all 16 participants, including teachers and staff, were able to effectively understand how to operate the system and enter data accurately. Furthermore, the system functioned well (valid) according to the partner’s needs, allowing the school's web profile information system to be published for the public, providing essential information about the school to the broader community.